PENERAPAN PSAK NO. 45 DALAM PELAPORAN KEUANGAN PANTI ASUHAN YAYASAN ISLAM MEDIA KASIH TAHUN 2017 - Wiladatika, Wiladatika; Diantimala, Yossi (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
There are lots of non-profit organization needs transparency and accountability in financial reports to engage donors to donate in Indonesia today. To support them, Ikatan Akuntan Indonesia has produced PSAK No. 45 about non-profit organization financial reports. This research placed in Yayasan Islam Media Kasih orphanage that has been one of non-profit organizations. The aim of this research is to identify whether the orphanage has applied PSAK No. 45 in their financial reports. Descripive research methods with qualitative analysis techniques outlines, describe and compare the data. The results showed they not match with the arranging of financial reports based on PSAK No. 45 formats. There are just revenue reports, expense reports, and balance sheets based form their own understanding. The Orphanage does not provide yet the reports o financial position, activity reports, cash flow reports, and the record of financial reports. Preferably, the orphanage provides the financial reports based on PSAK No. 45 to be more transparent and accountable so as to engage the donors.